The Impact of Including Advantaged Groups in Collective Action Against Social Inequality on Politicized Identification of Observers From Disadvantaged and Advantaged Groups. Issue 2 (14th June 2021) - Kutlaca, Maja; Radke, Helena R. M.; Becker, Julia C.
Abstract : Mobilizing public support is key to a movement's success. Little is known, however, about how movements can achieve this goal and whether involving advantaged group members is beneficial for a movement's cause. In a set of five experiments with convenience samples collected in the United States and Germany (total N = 1, 625), we examined whether protests (e.g., against racism and sexism) with and without advantaged group members affect politicized identification among observers. We expected that the presence (vs. absence) of advantaged group members at a protest will increase politicized identification among advantaged group observers, which was confirmed in Studies 1A–1C. In contrast, we expected that the disadvantaged group observers will increase or decrease their politicized identification depending on the role advantaged group members have at a protest (i.e., supportive vs. leadership role). Studies 2A–2B revealed that when advantaged group members had a supportive role, disadvantaged and advantaged group observers increased their politicized identification, but this effect was absent when they had a leadership role. Moreover, including advantaged group members in a protest increased the belief that solidarity is a normative behavior and the expectations that a protest will be peaceful among observers. Implications for research on allyship are discussed.